La atracción en la elección de pareja - Puma Simbrón, Hellen (2019)
The objective of the research is to analyze the role of attraction in mate choice and the factors that are involved inthe social context. This is a theoretical review article. It comes to physical attractiveness as an important elementwhen choosing a partner, as it impacts positively on people and this opens up more opportunities, but it should benoted that the concept of beauty depends on the social context and cultural. We conclude that the attraction is thestarting point when choosing a partner, this involves physical attractiveness and other similar factors, but must alsoconsider the social context (culture, customs, values, principles) that surrounds each individual, as this affects theirconcept of what is beautiful.